2020
DOI: 10.3390/nu13010097
|View full text |Cite
|
Sign up to set email alerts
|

Have Lifestyle Habits and Psychological Well-Being Changed among Adolescents and Medical Students Due to COVID-19 Lockdown in Croatia?

Abstract: Objective: To investigate dietary habits, sleep and psychological well-being of adolescents and medical students during COVID-19 lockdown in Split, Croatia. Methods: We surveyed 1326 students during 2018 and 2019, and compared their responses with 531 students enrolled in May 2020. Perceived stress, quality of life (QoL), happiness, anxiety, and optimism were assessed as proxies of psychological well-being, using general linear modelling. Results: We found no substantial differences in dietary pattern between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
146
5
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(181 citation statements)
references
References 70 publications
17
146
5
13
Order By: Relevance
“…Regarding the instruments used to evaluate the HRQoL, four different scales were used to evaluate the HRQoL of children and adolescents: KIDSCREEN-10 index, the SF-36, the Pediatric Quality of Life Inventory Questionnaire, and a Likert Scale (0–10). Three articles explicitly stated that used language validated versions [ 16 , 22 ] whereas the other three articles only described the questionnaire in their article [ 15 , 17 , 18 ]. To summarize, three articles reported that COVID-19 significantly reduced the HRQoL of children and adolescents [ 15 , 16 ], two articles did not find a significant impact [ 17 , 18 ], and one article did not report statistical comparison between pre- and post-pandemic data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the instruments used to evaluate the HRQoL, four different scales were used to evaluate the HRQoL of children and adolescents: KIDSCREEN-10 index, the SF-36, the Pediatric Quality of Life Inventory Questionnaire, and a Likert Scale (0–10). Three articles explicitly stated that used language validated versions [ 16 , 22 ] whereas the other three articles only described the questionnaire in their article [ 15 , 17 , 18 ]. To summarize, three articles reported that COVID-19 significantly reduced the HRQoL of children and adolescents [ 15 , 16 ], two articles did not find a significant impact [ 17 , 18 ], and one article did not report statistical comparison between pre- and post-pandemic data.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles explicitly stated that used language validated versions [ 16 , 22 ] whereas the other three articles only described the questionnaire in their article [ 15 , 17 , 18 ]. To summarize, three articles reported that COVID-19 significantly reduced the HRQoL of children and adolescents [ 15 , 16 ], two articles did not find a significant impact [ 17 , 18 ], and one article did not report statistical comparison between pre- and post-pandemic data. Differences between girls and boys were explored in two articles [ 16 , 22 ] and non-significant differences were observed in the effect of the COVID-19 pandemic on the HRQoL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coronavirus disease 2019 (COVID-19) pandemic and related restrictions have led to widespread changes; this also applies to lifestyles, including eating habits [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. So far, as a result of the pandemic, Japan has twice experienced a state of emergency.…”
Section: Introductionmentioning
confidence: 99%
“…Further, remote work and studying would affect mealtimes as well as the amount and type of food consumed. In fact, COVID-19-related studies have reported dietary behavior changes in children with obesity in Italy [ 1 ]; adolescents in Croatia [ 2 ]; adults in the USA [ 3 ], Denmark [ 4 ], France [ 5 ], Italy [ 6 ], Lithuania [ 7 ] and China [ 8 ]; and older adults in the Netherlands [ 9 ].…”
Section: Introductionmentioning
confidence: 99%